Finland : 2010 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Finland. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Owing to the high dependence of its exports on countries and commodities, Finland experienced the worst recession in the euro area. Executive Directors encouraged authorities to focus on improving bank cost efficiency, preventing excessive risk taking, and limiting liquidity and funding risks. Directors welcomed the establishment of the Nordic-Baltic Stability Group, and stressed the need to strengthen the effectiveness of cross-border supervision and crisis management arrangements. Directors welcomed structural reforms and also emphasized the need of a strong fiscal consolidation to secure fiscal sustainability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet